2019
DOI: 10.3390/cells8121514
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Protein Disulfide Isomerase Shapes T Cell Efficacy for Adoptive Cellular Therapy of Tumors

Abstract: Effective cancer therapies simultaneously restrict tumor cell growth and improve anti-tumor immune responses. Targeting redox-dependent protein folding enzymes within the endoplasmic reticulum (ER) is an alternative approach to activation of the unfolded protein response (UPR) and a novel therapeutic platform to induce malignant cell death. E64FC26 is a recently identified protein disulfide isomerase (PDI) inhibitor that activates the UPR, oxidative stress, and apoptosis in tumor cells, but not normal cell typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
1
13
1
Order By: Relevance
“…They identified the stress response p38 MAP kinase as a key driver involved in preventing T cell mediated tumor immunity (155). This finding reinforces previous studies that elegantly demonstrated that ER stress, a target regulated by p38, impairs intratumoral T cell protein translation of cytotoxic molecules and regulates mitochondrial and T cell exhaustion (156)(157)(158)(159). Nonetheless, the current efforts exploring inhibition of these key signaling pathways in vitro may provide TIL and CAR T cell with enhanced bioenergetics, persistence and anti-tumor capacity during their expansion.…”
Section: Inhibiting Signaling Pathways To Improve T Cell Therapiessupporting
confidence: 75%
“…They identified the stress response p38 MAP kinase as a key driver involved in preventing T cell mediated tumor immunity (155). This finding reinforces previous studies that elegantly demonstrated that ER stress, a target regulated by p38, impairs intratumoral T cell protein translation of cytotoxic molecules and regulates mitochondrial and T cell exhaustion (156)(157)(158)(159). Nonetheless, the current efforts exploring inhibition of these key signaling pathways in vitro may provide TIL and CAR T cell with enhanced bioenergetics, persistence and anti-tumor capacity during their expansion.…”
Section: Inhibiting Signaling Pathways To Improve T Cell Therapiessupporting
confidence: 75%
“…PDIA5 regulates the unfolded protein response (UPR) signaling pathway by activating ATF6α ( 28 ), whereby UPR regulates tumor cell survival. Other research has found that PDI inhibition could impair tumorigenic T cells and enhance normal T cell function ( 29 ). Based on the aforementioned findings, we speculated that PDIA5 correlated with histopathology grades and immune infiltration of gliomas, and could be a potential prognostic molecule.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that artificial disulfide bond formation in extracellular proteins increases CP efficiency. Recent research has shown that PDI inhibitors induce cancer-specific apoptosis in addition to the activation of cancer-specific T cells and the expansion of memory T cells in a mouse model [136]. In this experiment, cancer-specific T cells were activated by the addition of cancer-specific peptides; therefore, this is not the result of the progression of CP efficiency.…”
Section: Recognition Of Extracellular Proteins As Erad Substratesmentioning
confidence: 96%